2011
DOI: 10.1186/1471-2350-12-108
|View full text |Cite
|
Sign up to set email alerts
|

The first report of RPSA polymorphisms, also called 37/67 kDa LRP/LR gene, in sporadic Creutzfeldt-Jakob disease (CJD)

Abstract: BackgroundAlthough polymorphisms of PRNP, the gene encoding prion protein, are known as a determinant affecting prion disease susceptibility, other genes also influence prion incubation time. This finding offers the opportunity to identify other genetic or environmental factor (s) modulating susceptibility to prion disease. Ribosomal protein SA (RPSA), also called 37 kDa laminin receptor precursor (LRP)/67 kDa laminin receptor (LR), acts as a receptor for laminin, viruses and prion proteins. The binding/intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…LRP/LR acts as a receptor for PrP C and PrP Sc ( 106 , 107 ). Four RPSA SNPs (5' UTR-8T>C, 134-32C>T, 519G>A, and 793+58C>T) were not linked to sporadic CJD susceptibility ( 108 ).…”
Section: Polymorphisms In Other Candidate Genesmentioning
confidence: 99%
“…LRP/LR acts as a receptor for PrP C and PrP Sc ( 106 , 107 ). Four RPSA SNPs (5' UTR-8T>C, 134-32C>T, 519G>A, and 793+58C>T) were not linked to sporadic CJD susceptibility ( 108 ).…”
Section: Polymorphisms In Other Candidate Genesmentioning
confidence: 99%
“…These possible polymorphic amino acids cannot be confirmed by any EST of the NCBI databank. In the human mutation study 4 SNPs were observed, including a synonymous one in the coding region (exon 5) (Yun et al, 2011). An association study with sporadic Creutzfeldt-Jakob disease found no significant associations.…”
Section: Mutation Detection Of the Rpsa Gene In Sheepmentioning
confidence: 99%
“…We used previously established criteria [19] for diagnosis of sporadic CJD in Korea. The sporadic CJD cases in Korea have been reported previously [20,21,22]. The study was approved by the Ethical Committee of Hallym University Sacred Heart Hospital and informed consent was given by all subjects or their caregivers.…”
Section: Methodsmentioning
confidence: 99%